Engineering Saccharomyces cerevisiae for the de novo Production of Halogenated Tryptophan and Tryptamine Derivatives. Issue 4 (16th March 2023) - Milne, Nicholas; Sáez‐Sáez, Javier; Nielsen, Annette Munch; Dyekjær, Jane Dannow; Rago, Daniela; Kristensen, Mette; Wulff, Tune; Borodina, Irina
Abstract: The indole scaffold is a recurring structure in multiple bioactive heterocycles and natural products. Substituted indoles like the amino acid tryptophan serve as a precursor for a wide range of natural products with pharmaceutical or agrochemical applications. Inspired by the versatility of these compounds, medicinal chemists have for decades exploited indole as a core structure in the drug discovery process. With the aim of tuning the properties of lead drug candidates, regioselective halogenation of the indole scaffold is a common strategy. However, chemical halogenation is generally expensive, has a poor atom economy, lacks regioselectivity, and generates hazardous waste streams. As an alternative, in this work we engineer the industrial workhorse Saccharomyces cerevisiae for the de novo production of halogenated tryptophan and tryptamine derivatives. Functional expression of bacterial tryptophan halogenases together with a partner flavin reductase and a tryptophan decarboxylase resulted in the production of halogenated tryptophan and tryptamine with chlorine or bromine. Furthermore, by combining tryptophan halogenases, production of di‐halogenated molecules was also achieved. Overall, this works paves the road for the production of new‐to‐nature halogenated natural products in yeast. Abstract : Saccharomyces cerevisiae strains expressing several tryptophan halogenases, a flavin reductase, and a tryptophan decarboxylase are used for the in vivo biosynthesis of halogenated tryptophan and tryptamine derivatives. The products can serve as halogenated building blocks for the synthesis of pharmaceuticals or new‐to‐nature halogenated natural products.